Endovascular repair and management of a ruptured inferior pancreaticoduodenal artery aneurysm: A case report and literature review - Pavel Kibrik, DO; Jerry Zhu, BS; Ajit Rao, MD; Daniel Han, MD; Peter Faries, MD; James Cornwall, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Inferior pancreaticoduodenal artery aneurysm (IPDA) with the stenosis of the celiac axis is rare and may cause rupture. A unique etiology of IPDAs with celiac stenosis is median arcuate ligament syndrome. These aneurysms develop as a result of the dilation of the arteries from the retrograde blood flow into the pancreaticoduodenal arches because of celiac artery compression by the median arcuate ligament. We describe a 39-year-old man whose ruptured IPDA was associated with celiac artery stenosis and who was managed with coil embolization. The patient has agreed to have their case details and images published.